Objetos digitais de aprendizagem de História do Brasil para o Ensino Médio: uma proposta de roteiro avaliativo para o professor-curador - Souza, Renato Fontes de (2017)
This research integrates the New Technologies in Education line of the postgraduate program in Education: Curriculum, from PUC / SP, and is about the Digital Learning Objects (ODA) of History of Brazil for High School. From the problem question, "What criteria can History teachers use to select digital learning objects from History of Brazil for High School?", This research with a qualitative approach carried out a documentary analysis and aimed to present a history of the teaching of History in Brazil; propose the organization of a script for the analysis of digital learning objects of this discipline for High School; raise and analyze examples of ODA from the elaborate script and indicate possible paths for curating digital learning objects by History teachers. The data collected allowed the development of a roadmap for the identification, analysis and selection of digital learning objects according to technical, conceptual and pedagogical criteria in order to integrate these materials into pedagogical practice. The data also point out ways that can contribute to the teaching of History of Brazil with the use of digital information and communication technologies